RADT-07. RADIOGRAPHIC "NECROSIS" FOLLOWING SINGLE-FRACTION SRS AND IMMUNE CHECKPOINT INHIBITION IS ASSOCIATED WITH IMPROVED SURVIVAL IN PATIENTS WITH BRAIN METASTASES: AN INTERNATIONAL MULTICENTER STUDY. (14th November 2022) - Lehrer, Eric; Ahluwalia, Manmeet; Gurewitz, Jason; Bernstein, Kenneth; Kondziolka, Douglas; Wei, Zhishuo; Niranjan, Ajay; Lunsford, L Dade; Fakhoury, Kareem; Rusthoven, Chad; Mathieu, David; Trudel, Claire; et al.
Abstract: OBJECTIVE: Immune checkpoint inhibitors (ICI) and stereotactic radiosurgery (SRS) are commonly utilized in the management of brain metastases. Treatment-related imaging changes (TRIC) are a frequently observed clinical manifestation and are commonly classified as radiographic radiation necrosis. However, these findings are not well characterized and may predict for response to SRS and ICI. METHODS: The diagnosis-specific graded prognostic assessment was used to guide variable selection. TRIC were determined based upon MRI, PET/CT, or MR spectroscopy and a consensus by local clinical providers was required. RESULTS: The analysis included 697 patients with 4, 536 brain metastases across 11 institutions in 4 countries. The median follow-up after SRS was 13.6 months. The median age was 66 years, 54.1% of patients were male, and 57.3%, 36.3%, and 6.4% were non-small cell lung cancer, melanoma, and renal cell carcinoma (RCC) histology, respectively. TRIC were observed in 9.8%. On univariable analysis, Karnofsky Performance Status (KPS) (hazard ratio [HR]: 0.98; p < 0.001), presence of TRIC (HR: 0.67; p = 0.03), female sex (HR: 0.67; p < 0.001), and prior resection (HR: 0.60; p = 0.03) were associated with improved OS. On multivariable analysis, KPS (HR: 0.98; p < 0.001) and the presence of TRIC (HR: 0.66; p = 0.03) were associated with improved OS. A V12 Gy ≥ 10 cm 3 (Odds Ratio [OR]: 2.78; p < 0.001), prior whole brain radiation therapy (OR: 3.46; p = 0.006), and RCC histology (OR: 3.10; p = 0.01) were associated with an increased probability of developing TRIC. The median OS in patients with and without TRIC was 29.0 and 23.1 months, respectively (log-rank p = 0.03). CONCLUSION: TRIC following ICI and SRS are associated with a median OS benefit of approximately 6 months. Further prospective study is warranted to further elucidate the role and etiology of this common clinical scenario.